The Influence of Perceived Price Justice and Satisfaction on the Loyalty of Breast Cancer Care Alliance (BCCA) Siloam Hospital Semanggi Patients with Revisit Intention as Mediation - Nathania, Sarah Nurina; Wuisan, Dewi; Yuliana, Merryl Esther (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2023)
Purpose - The purpose of this study is to analyze the effect of Perceived Price Justice, and Satisfaction on patient's Loyalty with Revisit Intention as mediation.Design/Methodology/Approach - The method applied in this research is a quantitative approach with a google forms questionnaires, distributed to respondents who are patients in Breasts Cancer Care Alliance (BCCA) Siloam Hospital Semanggi. The number of samples used was 160 respondents, then analyzed through PLS-SEM using SmartPLS 3.0.Findings - The results of this study prove that the perceived price justice variable has an indirect positive influence on loyalty if it is followed with revisit intention as a mediation. On the other hand, this study also shows that the perception satisfaction variables has an indirect positive influence on loyalty with revisit intention as a mediation.Research Limitations/Implications - The main limitation of this study is using an online questionnaire to collect data, which limits supervision in the data entry process to ensure whether the data given is correct according to the directions.Practical Implications - The results of this study prove that the perception price justice variables has an indirect positive influence on loyalty if it is followed with revisit intention US a mediation. On the other hands, this study also shows that the perceived satisfaction variable has an indirect positive influence on loyalty with revisit intention as a mediation. This research is expected to be able to contribute to research that has been done previously, and also to other communities who may be conducting research with the same model or variables.Originality/Value - This study uses the same variables as previous research. The study aims to advise and give insight to BCCA Siloam Hospital Semanggi, in order to develop their marketing especially in the field of management. This research is expected to be able to contribute to research that has been done previously, and also to other communities who may be conducting research with the same model or variables.